Variasi bentuk dan pembeda makna gatra sifat yang bersinonim dalam bahasa Rejang isolek Talang Boseng - Nadra, Nadra; Noviatri, Noviatri; Juwita, Tiara (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2025)
This research aims to explain the form, semantic components, and distinguishing features of synonymous adjectives in the Rejang language, based on a study in Talang Boseng Village, Pondok Kelapa District, Central Bengkulu. A descriptive research design with a qualitative approach was employed. Data collection involved interview and observation methods. For data analysis, translational equivalence, distributional, and componential analysis methods were utilized. The distributional method was applied using substitution and expansion techniques. The findings reveal two forms of synonymous adjectives: word-to-word and word-to-phrase. The semantic components of these synonymous adjectives can be categorized into four groups: (1) tending to be similar, (2) tending to be different, (3) exactly the same, and (4) an equal number of similarities and differences. Nine factors differentiating the meanings of these synonymous adjectives were identified: (1) one is more general, (2) more intensive, (3) more emotive, (4) more professional, (5) encompasses acceptance and rejection, (6) more colloquial, (7) local or regional in nature, (8) differences in application, and (9) differences in implication. The distinctiveness of adjectives in the Talang Boseng isolect of the Rejang language is evident in the semantic differences arising from variations in application, which can be further subdivided into temporal and object applications.